Field study on the accumulation of trace elements by vegetables produced in the vicinity of abandoned pyrite mines - Alvarenga, Paula (2013)
To evaluate the accumulation of trace elements (TE) by vegetables produced in the vicinity of abandoned pyrite mines, eighteen different small farms were selected near three mines from the Portuguese sector of the Iberian Pyrite Belt (São Domingos, Aljustrel and Lousal). Total and bioavailable As, Cu, Pb, and Zn concentrations were analyzed in the soils, and the same TE were analyzed in three different vegetables, lettuce (Lactuca sativa), coriander (Coriandrum sativum), and cabbage (Brassica oleracea), collected at the same locations. The soils were contaminated with As, Cu, Pb, and Zn, since their total concentrations exceeded the considered soil quality guideline values for plant production in the majority of the sampling sites. The maximum total concentrations for those TE were extremely high in some of the sampling sites (e.g. 1851 mg As kg− 1 in São Domingos, 1126 mg Cu kg− 1 in Aljustrel, 4946 mg Pb kg− 1 in São Domingos, and 1224 mg Zn kg− 1 in Aljustrel). However, the soils were mainly circumneutral, a factor that contributes to their low bioavailable fractions. As a result, generally, the plants contained levels of these elements characteristic of uncontaminated plants, and accumulation factors for all elements < 1, typical of excluder plants. Furthermore, the estimated daily intake (EDI) for Cu and Zn, through the consumption of these vegetables, falls below the recommended upper limit for daily intake of these elements. The sampling site that stood out from the others was located at São João de Negrilhos (Aljustrel), where bioavailable Zn levels were higher, a consequence of the slight acidity of the soil. Therefore, the Zn content in vegetables was also higher, characteristic of contaminated plants, emphasizing the risk of Zn entering the human food chain via the consumption of crops produced on those soils.